A Review on Traditional and Alteranative Treatment For Skin Disease â€œVitiligoâ€ - Soni, Priyanka (International Journal of Pharmaceutical & Biological Archive, 2010)
Vitiligo is a relatively common dermatologic finding and one that has been observed since ancient times.Vitiligo is characterized by white (depigmented) patches in the skin, caused by the loss of functioning melanocytes. The hair, and rarely the eyes may also lose colour. Vitiligo is a relatively common dermatologic finding and one that has been observed since ancient times. The cause of vitiligo remains unknown, although an autoimmune pathogenesis seems most likely. Treatment also remains difficult, allopathic are only suppressive therapy not curative. A number of new therapies show significant potential. In this review, we will focus on the traditional remedies, herbs reported as antivitiligo agents, surgical treatments, ayurvedic and alternative treatment for vitiligo.